Interpretasi Fazlur Rahman Atas Isu Poligami (Studi Analisis Q.S An-Nisa: 3) - Hayati, Ridha (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2018)
This paper discusses the debate on interpretation of Q.S. An-Nisa: 3 which often used as an argument for polygamy. The problem that arises from that interpretation is the emergence of “naughty” perspectives from of most of the men. The resulting consequences are the occurrence of disharmony and even bring up conflicts that often involve children as victims. Because we live in a complex era of polemics that arise, it is important to solve the problem by looking at the thinking of contemporary scholars who are expected to provide solutions to the problems of the ummah. Therefore, to respond to the problem, the writer takes Fazlur Rahman's thought as a related analysis blade Q.s. An-Nisa: 3 which becomes the central verse in the discussion of polygamy, by looking at the socio-historical context of the decline of the verse through his double-movement theory. From these methods it can be seen that the marriage that the al-Qur'an aspired to is a monogamous marriage.